2012
DOI: 10.1099/jmm.0.042374-0
|View full text |Cite
|
Sign up to set email alerts
|

Natural and experimental Helicobacter pullorum infection in Brown Norway rats

Abstract: Helicobacter pullorum is an enterohepatic Helicobacter species (EHS) that was recently reported as a naturally acquired infection in mice. Faecal samples from 18 out of 20 Brown Norway (BN) rats, housed in the same barrier as the H. pullorum-infected mice, were positive for H. pullorum using species-specific PCR. In addition, we determined whether H. pullorum was able to persistently colonize the gastrointestinal tract and/or biliary tree and elicit tissue inflammation as well as a serum IgG response in BN rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The infection has been linked to vibrionic hepatitis lesions in chickens (Burnens et al, 1994) and diarrhea in humans (Ceelen et al, 2005a). Meanwhile, natural infection of H. pullorum strains in rats and rabbits has also been reported (Van den Bulck et al, 2006; Cacioppo et al, 2012). H. pullorum prevalence reports from various regions have been summarized in Table 1.…”
Section: Prevalencementioning
confidence: 97%
“…The infection has been linked to vibrionic hepatitis lesions in chickens (Burnens et al, 1994) and diarrhea in humans (Ceelen et al, 2005a). Meanwhile, natural infection of H. pullorum strains in rats and rabbits has also been reported (Van den Bulck et al, 2006; Cacioppo et al, 2012). H. pullorum prevalence reports from various regions have been summarized in Table 1.…”
Section: Prevalencementioning
confidence: 97%
“…Immunohistochemical examination revealed that the bacterium was closely associated with cecal epithelial cells. Cacioppo et al (2012) observed that Brown Norway rats were persistently colonized by H. pullorum and had a sustained H. pullorum-specific IgG response measured by ELISA. Cacioppo et al (2012) did not find intestinal or hepatic pathology associated with H. pullorum.…”
Section: Clinical Relevancementioning
confidence: 97%
“…Cacioppo et al (2012) observed that Brown Norway rats were persistently colonized by H. pullorum and had a sustained H. pullorum-specific IgG response measured by ELISA. Cacioppo et al (2012) did not find intestinal or hepatic pathology associated with H. pullorum. Ceelen et al (2006) examined 10 poultry and three human isolates of H. pullorum for the presence and activity of CDT.…”
Section: Clinical Relevancementioning
confidence: 97%
“…have been found as natural infections of rats. Persistent infection of Brown Norway rats was also established by oral inoculation (Cacioppo et al, 2012b). H. trogontum has now been identified as LABORATORY ANIMAL MEDICINE the most prevalent of the naturally occurring intestinal helicobacters (Mendes et al, 1996) in rats, and H. bilis has been reported from the large bowel of immunodeficient rats (Haines et al, 1998).…”
Section: Helicobacteriosismentioning
confidence: 99%